Antibacterial Activity of Herbal Tea Extract from Lotus Leaves (Nelumbo nucifera) Using Different Solvents - Syifa, Muhammad; Khairina, Rita; Puspitasari, Findya (Jurnal Agrotek Ummat, 2024)
This research aimed to examine the antibacterial activity of lotus leaf (Nelumbo nucifera) extract as a basis for herbal tea production. Lotus leaf was chosen as the herbal tea ingredient due to its abundant availability in South Kalimantan and its believed beneficial phytochemical content for health. The research process involved several stages including lotus leaf herbal tea processing, multi-stage maceration extraction using hexane, ethyl acetate, and ethanol solvents, and testing the extract's ability against Escherichia coli bacteria. The research design employed a 2-factor complete randomized design, with the first factor being the extract concentration and the second being the solvent type. Data analysis was conducted using Two-Way ANOVA in IBM SPSS 25. The results revealed that ethanol solvent produced the highest concentration extract with a yield of 10.86%, while hexane solvent yielded the lowest at 1.64%. Subsequent antibacterial activity testing was carried out using direct contact method with lotus leaf extract concentrations of 0.5%, 1%, and 1.5% in all three solvents. The findings indicated that 0.5% and 1% concentration extracts inhibited Escherichia coli growth across all solvents, whereas the 1.5% extract concentration in ethanol was capable of killing Escherichia coli bacteria. It was concluded that lotus leaf extract holds potential as an antibacterial agent, with higher extract concentrations showing greater efficacy in inhibiting bacterial growth. The 1.5% concentration (45 μl) exhibited the most effective results in killing Escherichia coli, underscoring the potential of Nelumbo nucifera lotus leaf in the development of antibacterial herbal products.